Multivariable mathematics - Moreira, Olga
Presents a collection of contemporary articles combines several topics of multivariate mathematics, from extensions of uni-variate methodologies to practical applications in several research areas of multivariate calculus, statistical analysis, time series, polynomial geometry and differential topology.